Peran Wakaf Tunai Dalam Pengembangan Ekonomi Pondok Pesantren Darul Hijrah Di Sungai Rengas Kabupaten Batanghari - Olivia Pebrianti; Suhar Suhar; Eri Nofriza (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research is entitled The Role of Cash Waqf in the Economic Development of the Darul Hijrah Islamic Boarding School on the Rengas River, Batanghari Regency. The aims of this study are: 1) To find out how cash waqf is managed at the Darul Hijrah Islamic Boarding School. 2) To find out the role of cash waqf in the economic development of the Darul Hijrah Islamic Boarding School. The research method used by researchers is a qualitative approach. The results of this study are: 1) In the process of managing waqf funds at the Darul Hijrah Islamic Boarding School, the fund management function starts from planning to realization. These stages are applied in every waqf fundraising process, the business preparation process, the placement of workers to the allocation of operating proceeds. In the implementation of waqf fund planning at the Darul Hijrah Islamic Boarding School, including: Planning for types of business, Planning for waqf sources, Planning for managing the business needed, and Planning for income to be obtained and where to distribute it. The source of cash waqf funds at the Darul Hijrah Islamic Boarding School comes from the waqf of the local government, parents of students and the general public. While the types of Islamic boarding school economic businesses funded by waqf funds are oil palm plantations, canteen businesses and buffalo livestock. 2) The forms of waqf in the Darul Hijrah Islamic Boarding School are in the form of cash waqf, immovable waqf. Waqf of immovable objects in the form of palm oil fields and buffalo livestock. In addition, the waqf received is also in the form of cash and other objects such as building materials, food ingredients and Al-Quran manuscripts. This form of waqf is used for, 1) Development of Islamic boarding schools, 2) Consumption of students, 3) Learning facilities and infrastructure, 4) Honorarium of teachers and 5) Economic activities of Islamic boarding schools. 3) The existence of waqf funds at the Darul Hijrah Islamic Boarding School plays a very important role for the economy of the pesantren residents at the Darul Hijrah Islamic Boarding School in 3 ways, namely, firstly creating jobs for the students and for the pesantren's teachers, secondly increasing income for the students, teachers and the pesantren itself to meet daily needs and help meet the needs of Islamic boarding schools, thirdly increasing business capabilities for Islamic boarding school students and teachers in terms of sales, business and business management. As a result, the role of the waqf is able to increase the economic independence of the Darul Hijrah Islamic Boarding School in the income of students and teachers, honorariums for teachers, and consumption as well as the development of Islamic boarding schools.